Design of a Fire Warning Prototype System at PT. Sevta Nusa Energi Using N Sensor Modules - Anastasya Sa’adah; Saludin Muis (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
Fire is an unexpected disaster and can occur at any time, often due to human negligence. Data from the Bogor Regency Fire Department shows an increase in the number of fires, especially in industrial and commercial areas, with a total of 280 cases in 2023, including 170 cases in Bogor City, which increased significantly from 172 cases in 2022. PT Sevta Nusa Energi, which is engaged in convection, merchandising, and Event Organizer, stores various materials and equipment that have the potential to catch fire. To reduce the risk of fire, an advanced fire detection system can be a solution, using technologies such as fire sensors, automatic alarms, and Internet of Things (IoT) connectivity to provide early warning to warehouse management and emergency response teams. The use of KY-026 sensors to detect fire, as well as DHT22 sensors to measure temperature and humidity, allows for accurate and fast data collection, so that preventive measures can be taken immediately. Based on this explanation, a title was made, Designing a Fire Early Warning System at PT Sevta Nusa Energi Using N Sensor Modules.